Sports nutrition essentials - Bell-Wilson, Jenna; American College of Sports Medicine (Indianapolis, In. : Montery Bay Video Production Co., 2006)
Sports nutrition essentials details the key elements involved in proper nutrition, including nutrient needs, metabolism basics, and supplement use
Keywords: Athletes -- Nutrition; Nutrition